Ortho-Substituent effect on the crystal packing and solid state speciation of aromatic C-nitroso compounds. Issue 30 (16th July 2020) - Pike, Sarah J.; Heliot, Armelle; Seaton, Colin C.
Abstract : The solid state behaviour of a short series aromatic C -nitroso compounds has been studied as a function of the electronic and steric nature of the ortho -substituent on the ring. Abstract : The solid state behaviour of a short series of aromatic C -nitroso compounds bearing a range of ortho -substituents, including amides, alcohols, methyl and fluorine have been investigated using single crystal X-ray diffraction. Solid state analysis has confirmed the contrasting speciation behaviour of aromatic C -nitroso compounds incorporating strongly and weakly electron-donating groups at the ortho -position with the former group adopting monomers or oxo-oxime tautomers whilst the latter group adopts either the cis - or trans -azodioxy dimer depending on the nature of the solvent employed in the crystallisation conditions. The presence of weakly electron-withdrawing fluorine substituents on the nitrosoarene leads to the formation of the trans -azodioxy dimer. Single crystal X-ray diffraction analysis has identified the presence of a diverse array of hydrogen-bonding interactions and π–π stacking interactions that support the adoption of a range of supramolecular aggregates, including chains and tunnels, in the crystal packing of this small library of aromatic C -nitroso compounds.